Measurement of the forward-backward asymmetries in the production of Ξ and Ω baryons in p p collisions MEASUREMENT of the FORWARD-BACKWARD ⋯ V. M. ABAZOV et al. - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Agnew, J. P.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Askew, A.; Atkins, S.; Augsten, K.; et al. (My University, 2016)
We measure the forward-backward asymmetries AFB of charged Ξ and Ω baryons produced in pp collisions recorded by the D0 detector at the Fermilab Tevatron collider at s=1.96 TeV as a function of the baryon rapidity y. We find that the asymmetries AFB for charged Ξ and Ω baryons are consistent with zero within statistical uncertainties.